NUMERICAL SIMULATION STUDY ON COAL AND ROCK CRUSHING OF COAL PLOUGH - HAO ZhiYong; WANG ShuaiLing; CHEN ZhiQiang; YUAN Zhi (Jixie qiangdu)
In order to study the crushing process and its influencing factors of the coal rock ploughing and planing by the plough cutters,the planing process is analyzed by numerical simulation, in view of the fact that coal and rock are heterogeneous media, coal rock images are identified, the three-dimensional model of coal rock is established by image reconstruction method, the accuracy of simulation is increased, it provides a new theory and method for three-dimensional finite element modeling of heterogeneous materials, and obtains more accurate simulation data. Through the simulation of coal crushing process under different conditions of plow bit,get contact force plow bit and simulation of coal wall. The results show that:with the increase of planing depth, plow bit stress force increase, the stress gradually stabilized,but because of the change of the coal quality, the forces fluctuate up and down near a steady value;planing speed has little effect on the plane load;coal rock firmness coefficient is larger,the greater the load simulation tool.